Phenytoin Toxicity with High Dose, Concomitant Ascorbic Acid Dosing - Michael J. Schuh; Kevin Mustain; Sheena Crosby (University of Minnesota Libraries Publishing, 2022)
High dose ascorbic acid may increase risk of phenytoin toxicity. This case report demonstrates high phenytoin levels resulting in adverse drug reactions subsequent to dosing concomitantly with high dose vitamin C, or ascorbic acid (AA), as a precaution against acquiring corona virus (COVID) infection. This patient suffered from a major seizure when he ran out of his phenytoin prescription. Subsequent initiation of phenytoin and later addition of high dose AA resulted in truncal ataxia and falls with bilateral wrist and finger extension weakness. Phenytoin and AA were discontinued, and the patient returned to baseline on a new medication regimen of lacosamide and gabapentin without any other major seizures one year later.